Salt intake and reproductive function in sheep - S.N. Digby; M.A. Chadwick; D. Blache (Animal, 2011)
Producers have the possibility to combat human-induced dryland salinity by planting salt-tolerant plants such as saltbush. Saltbush has the potential to be used as a source of food for livestock at a time and place where pasture is not viable. However, saltbush contains high concentrations of sodium chloride salt and some other anti-nutritional factors that have the potential to affect feed and water intake and, directly or indirectly, the reproductive capacity of sheep. High-salt diet during gestation induces a small modification of the activity of the renin-angiotensin system (RAS) that has an important role in the maintenance of the salt-water balance in non-pregnant and pregnant sheep. In contrast, the main effect of salt ingestion during pregnancy is observed on the biology of the offspring, with changes in the response of the RAS to salt ingestion and altered thirst threshold in response to an oral salt ingestion. These changes, observed later in life, are the result of fetal programming following the ingestion of salt by the mother. It seems that the exposure to salt during pregnancy could provide an advantage to the offspring because of this adaptive response. The response may be particularly useful, for example, when grazing herbivores are fed halophytic forages adapted to saline soils.